Clinical outcome, PDGFRβ and KIT expression in feline histiocytic disorders: a multicentre study. (9th February 2015) - Treggiari, E.; Ressel, L.; Polton, G. A.; Benoit, J.; Desmas, I.; Blackwood, L.
Abstract: Information about histiocytic disease in cats is limited. The aim of this study was to document clinical findings and outcome in feline histiocytic disorders, and characterize the expression of PDGFRβ and KIT in order to identify potential treatment targets. Morphologically diagnosed feline histiocytic tumours were reviewed and characterized by immunohistochemistry (IHC). Five cases of feline progressive histiocytosis (FPH), eight histiocytic sarcomas (HS) and two haemophagocytic histiocytic sarcomas (HaeHS) were confirmed. PDGFRβ was variably positive in most histiocytic cases, while KIT was negative in all. Clinical presentation, treatment and outcome were also evaluated. Partial responses were recorded in measurable disease with tyrosine kinase inhibitors and lomustine, and radiotherapy achieved long‐term control in some cases. Survival times were shortest in HaeHS and disseminated disease. PDGFRβ, but not KIT, may represent a therapeutic target in feline histiocytic disorders but more studies are needed to investigate other potential treatment targets.